Pengembangan Materi Pendidikan Kecakapan Hidup pada Buku Pelajaran Bahasa Inggris dengan Model Pembelajaran Literasi pada Kelas X MAN Mojosari dan MAN Sooko Mojokerto - Mohammad Rodhi (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Modification matter of Life skills education in English textbooks with literacy learning model into the model lessons interesting and assist the teachers in improving the effectiveness of learning, it would require an innovative learning model literacy learning model.Products literacy teaching model of English in Class X MAN Mojosari and MAN Sooko District of Sooko Mojokerto has been refined based on analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products are revised based on the results of the theoretical and empirical test are: a) Revision RPP / Scenario Learning by Expert: Operational learning steps need to be revised, b) Revised Student Worksheet (LKS) by experts: Adequacy of time for each step needs to be revised, c) Revision by students by questionnaire: (1) Changing the way of evaluation in the use of the model. (2) Improve the look of the model or replacing the learning strategy. 2) The products developed interesting for classical learning in the classroom and independently. 3) The product of these products can ease the burden of teachers in teaching. 4) The results of expert validation and testing, literacy learning model is fit for use for subjects in English. 5) Products that are developed can enhance students' motivation, and motivation is one of the requirements of the implementation of productive learning model.